\[S\ =\ -\sum_i P_ilogP_i\] \[\begin{equation} 2=1+1 \end{equation}\] \[E\ =\ mc^2\] \[\begin{align*} & \phi(x,y) = \phi \left(\sum_{i=1}^n x_ie_i, \sum_{j=1}^n y_je_j \right) = \sum_{i=1}^n \sum_{j=1}^n x_i y_j \phi(e_i, e_j) = \\ & (x_1, \ldots, x_n) \left( \begin{array}{ccc} \phi(e_1, e_1) & \cdots & \phi(e_1, e_n) \\ \vdots & \ddots & \vdots \\ \phi(e_n, e_1) & \cdots & \phi(e_n, e_n) \end{array} \right) \left( \begin{array}{c} y_1 \\ \vdots \\ y_n \end{array} \right) \end{align*}\] \[\begin{equation} S_{\text{latency}}(s) = \frac{1}{(1-p)+\frac{p}{s}} \end{equation}\]